Balancing Medical Knowledge with Behavioral Strategies: Content Characteristics of High-Performing Pediatric Diabetes Videos on Indonesian TikTok - Rahayu, Agustin Putri; Rahayu, Eka Putri; Ariyanti, Rea (Panakeia Journal of Epidemiology, 2025)
Pediatric diabetes has become rapidly growing, with epidemiological projections indicating that nearly half of children with type 1 diabetes remained undiagnosed globally, while type 2 diabetes prevalence among youth increased more markedly than type 1 diabetes in several regions. This research aimed to conduct a comprehensive content analysis of the fifteen most highly engaged pediatric diabetes educational videos on TikTok within the Indonesian digital landscape over the past six months. The research method employed a quantitative content analysis design conducted on May 28, 2025, analyzing TikTok content using the keyword "diabetes anak" within the Indonesian digital domain. Results showed that documentary content dominated (93.3%), with "Foundational Medical Knowledge" and "Behavioral Health Management" each appearing in 66.7% of videos, while "Optimistic Messaging" and "Self-Efficacy Enhancement" were each present in 60% of content. Word cloud analysis revealed that practical diabetes management terminology such as "insulin," "diabetes," "makanan" (food), and "anak-anak" (children) dominated transcripts. Successful pediatric diabetes educational content on TikTok combined medical accuracy with authentic narratives and empowerment-focused messaging to achieve optimal audience engagement. Keywords: pediatric diabetes, TikTok, content analysis, digital health education